The Phaedo and the Education for (non-)death in 15th century Spain - Fernandes, Edrisi (Revista Archai, 2016)
Based on the Castillan translation of the Phaedo (1446”‘47, from the Latin version of Leonardo Bruni [Leonardo d’Arezzo/Arecio; Leonardo Aretino]) by Pero Díaz de Toledo (c. 1410”‘1466), his translation of the Axiocus (c. 1444”‘45; maybe the first philosophical treatise translated into a Neolatin language, from the Latin version of Cencio de’ Rustici, up to 1437) as well as his Diálogo y Razonamiento en la muerte del marqués de Santillana (up to 1460), we have analysed the problem of the “education for death” and the teaching about the immortality of the soul in XVth century Spain. Díaz de Toledo was chosen by King Juan II, with the support of Dom Íñigo López de Mendoza, Señor de la Vega and (after 1445) Count of the Real de Manzanares and Marquis of Santillana, to translate and write some texts that would be useful to the education of prince Enrique (the future king Enrique IV). This is the context in which the works mentioned above have been produced (and also a translation and gloss to the Proverbios de [of the pseudo”‘ ] Séneca, between 1442 e 1446). Díaz de Toledo understood the pseudo”‘Platonic Axiocus mainly as an iniciative to prove the “inmortalidat de la ánima”, and he used his translation of the Phaedo in order to refute the belief that the soul dies with the body. Also, in the first part of his Diálogo y Razonamiento (chapters 1”‘11, of 21), he used part of his translations of the Axiocus and of the Phaedo in the conversation with the dying marquis. The didactic endeavor of D íaz de Toledo contributed to the construction of Plato’s image as the pagan thinker, “philósopho sin fe, solamente atraído por la razón e lunbre natural” (from Díaz de Toledo introducion to the Phaedo), that was closer to the truths of the Bible and Christianism, especially concerning the representation of life beyond the grave, when the men “que derechamente filosofaran, e murieron de todo en todo puros e limpios”, are “trasladados en linaje [lineage] de dioses” (trad. do Phd. 82b), “son fechos [hechos] santos, e así son dioses por participación e non por exencia [esencia]” (gloss from Díaz de Toledo).